1996
DOI: 10.1046/j.1365-2141.1996.d01-1934.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary proliferating immature myeloid cells from CML patients are not resistant to induction of apoptosis by DNA damage and growth factor withdrawal

Abstract: Induction of apoptosis by growth factor deprivation or gamma-irradiation-induced DNA damage was directly studied in proliferating primary haemopoietic cells derived from CD34-positive cells of 13 CML patients and 12 normal controls. CD34-positive cells were cultured in the presence of appropriate concentrations of SCF and G-CSF for 5-7 d. After gamma irradiation with 500 rad or growth factor deprivation, the fraction of apoptotic cells was assessed by two independent methods applying either measurement of cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…33 The heterogeneity of patient samples and the potential differences of BCR-ABL protein expression, which varies from one patient (and probably from one hematopoietic cell) to another, could explain discordant findings obtained with regard to the inhibition of apoptosis in primary patient samples. 9,10 Our model distinctly shows that: (1) BCR-ABL protein expression in a human hematopoietic cell line is not sufficient to induce growth factor independence; and (2) the anti-apoptotic effect of BCR-ABL is fully operational only when BCR-ABL is expressed at high levels. Our data confirm, therefore, for the first time in pluripotent human cells, the results obtained by Pierce et al 34 in the murine FDCP-mix cell line in which the tyrosine kinase activity of BCR-ABL was found to be compatible with growth factor dependence and differentiation ability.…”
Section: Figurementioning
confidence: 95%
See 1 more Smart Citation
“…33 The heterogeneity of patient samples and the potential differences of BCR-ABL protein expression, which varies from one patient (and probably from one hematopoietic cell) to another, could explain discordant findings obtained with regard to the inhibition of apoptosis in primary patient samples. 9,10 Our model distinctly shows that: (1) BCR-ABL protein expression in a human hematopoietic cell line is not sufficient to induce growth factor independence; and (2) the anti-apoptotic effect of BCR-ABL is fully operational only when BCR-ABL is expressed at high levels. Our data confirm, therefore, for the first time in pluripotent human cells, the results obtained by Pierce et al 34 in the murine FDCP-mix cell line in which the tyrosine kinase activity of BCR-ABL was found to be compatible with growth factor dependence and differentiation ability.…”
Section: Figurementioning
confidence: 95%
“…[1][2][3] It has been established that BCR-ABL triggers a variety of molecular events inside the target cell with activation of several molecular pathways such as RAS, PI-3K and CRK-L. 4 evance with regard to human CML in which there have been conflicting reports with regard to the anti-apoptotic effects of BCR-ABL. [7][8][9][10] Similarly, although BCR-ABL gene transfer induces growth factor independence in growth factor-dependent cell lines, human hematopoietic progenitors bearing the BCR-ABL translocation as assessed by PCR or FISH analyses are not growth factor-independent and present only subtle abnormalities such as Epo-independent erythroid colony growth 11 in the presence of Steel factor. 12 Anti-apoptotic activities of BCR-ABL have been shown to be reverted by inhibition of the tyrosine kinase activity of BCR-ABL.…”
Section: Introductionmentioning
confidence: 99%
“…62,63,73 Most but not all studies using p210 BCR/ABL expressing cell lines have demonstrated that BCR-ABL expression protects from apoptosis induced by physical and chemical stresses. [74][75][76][77][78] Additionally, chronic phase CML CD34 + cells undergo delayed apoptotic death upon cytokine withdrawal when compared with normal progenitors. [79][80][81] The use of antisense oligonucleotides against BCR-ABL could reverse the delay in apoptosis in CML cell lines.…”
Section: Decreased Apoptosismentioning
confidence: 99%
“…47 Furthermore, BCR-ABL contributes to apoptosis resistance in a dose-dependent manner and BCR-ABL expression increases with disease progression from chronic phase to blast crisis. [48][49][50][51][52][53][54][55] Transgenic CML mouse model research showed that targeted BCR-ABL expression in myeloid progenitors led to a chronic MPD, whereas targeted overexpression of Bcl-2, but not Ras or Myc, promoted progression to blast crisis. 56 It is noted that activation of the Wnt/b-catenin pathway leads to increased c-myc expression and ultimately results in upregulation of Bcl-2 SPOTLIGHT family proteins.…”
Section: Stem Cell Survivalmentioning
confidence: 99%